Sovereign Debt Restructuring - Kroszner, Randall S (American Economic Review, 2003)
Since the early 1980's, patterns of emergingmarket finance have changed significantly. Greater integration of capital markets and a trend toward a greater use of direct lending through bonds has led to relatively decreased use of indirect finance through syndicated bank loans. These changes have produced benefits to investors through opportunities for risk diversification and to emerging-market sovereign borrowers by increasing the investor base. The broadened investor base in bond financing, however, raises problems of coordination and collective action in the event of a sovereign borrower's default and restructuring. Now, three parties are involved in determining the debt markdown required to produce solvency: the debtor, creditors, and the global taxpayer through international financial institutions (IFI's). The complex relationships among the borrowers, creditors, and the global taxpayer have made restructuring obligations a costly and time-consuming exercise, especially with the possibility of holdouts. Both the sovereign borrower and its creditors have an incentive to avoid a restructuring in the hope of financial assistance from the global taxpayer. Sovereign governments may not undertake the politically painful steps involved in beginning a restructuring when there is always the hope that official assistance will be forthcoming. Creditors may not accept a reduction in the value of their claims, also in the hope that official assistance will be forthcoming. Costs of postponed and disorderly restructurings are real and substantial. Delays in restructuring can drain a country's resources and increase the ultimate costs of restoring financial sustainability. Creditors bear a burden as well, because the losses associated with the restructuring are reflected in values of